Penentuan ralat multipath bagi data cerapan GPS julat pseudo di stesen rujukan RTK (Real Time Kinematic) di Malaysia - Mardina Abdullah,; Norbahiah Misran,; Nor Nadira Mohammad Ariff, (2010)
Multipath is widely recognized as one of the main source of error in GPS applications. Multipath is the phenomenon whereby a signal arrives at a receiver via multiple paths attributable to reflection and diffraction. This paper describes the analysis of multipath error of pseudorange obtain from RTK reference station. RTK reference station consists of 27 GPS reference stations and these stations are strategically distributed across Malaysia. This research also identifies which RTK reference station are the most and least affected by multipath effect of both pseudo ranges at L1 (1575.42 MHz) and L2 (1227.60 MHz) of GPS signals. In this research, TEQC software is used to check the multipath effect of both signals. It is shown that the most affected GPS data for multipath at L1 is from Marang (MARG) station with a value 0.453 m and the least from Kuala Kubu Baru (KKBH) station with a value 0.332 m. The most affected at L2 is also from MARG station 0.666 m and the least from Pekan (PEKN) station 0.431 m. It is hoped that this research be very helpful in GPS navigation